2009
DOI: 10.1007/s10495-009-0370-6
|View full text |Cite
|
Sign up to set email alerts
|

An involvement of BDNF and PI3-K/Akt in the anti-apoptotic effect of memantine on staurosporine-evoked cell death in primary cortical neurons

Abstract: Memantine, a clinically used NMDA receptor antagonist possesses neuroprotective properties, but the exact mechanisms of its beneficial action on neuronal survival are poorly recognized. In the present study, some intracellular mechanisms of memantine effects on staurosporine-evoked cell death were investigated in primary cortical neurons. Memantine (0.1-2 muM) suppressed neuronal apoptosis evoked by staurosporine in 7 DIV cortical neurons, whereas other antagonists of NMDA receptor, MK-801 (1 muM) and AP-5 (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 61 publications
3
20
0
Order By: Relevance
“…54 Several NMDA receptor antagonists, including ketamine, memantine and MK-801, increased BDNF, which is necessary for their antidepressant responses. 55,56 Based on these findings and our observation that 7-CTKA enhanced mTOR function and increased postsynaptic protein levels, we hypothesize that 7-CTKA produces antidepressant response through multiple pathways just like other NMDA receptor antagonists.…”
Section: Discussionmentioning
confidence: 75%
“…54 Several NMDA receptor antagonists, including ketamine, memantine and MK-801, increased BDNF, which is necessary for their antidepressant responses. 55,56 Based on these findings and our observation that 7-CTKA enhanced mTOR function and increased postsynaptic protein levels, we hypothesize that 7-CTKA produces antidepressant response through multiple pathways just like other NMDA receptor antagonists.…”
Section: Discussionmentioning
confidence: 75%
“…Staurosporine (STS), a classical apoptotic stimulus that has been previously widely characterized to induce apoptosis in several different cell types including primary neuronal cultures, [25][26][27] was used to promote apoptosis in primary cultures of cortical neurons. In the present experiments, 1 μM STS induced neuronal death as demonstrated by a progressive increase in the number of pyknotic nuclei from 6 h of STS treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the anti-apoptotic factors Bcl-2 and p-Akt are upregulated in the fish retina 2-5 days after axotomy, whereas these anti-apoptotic proteins are rapidly downregulated in the rat retina after nerve crush. The upregulation of Bcl-2 and p-Akt in the fish retina is mediated by the activation of the phosphatidylinositol-3-kinase/Akt signaling pathway through insulin-like growth factor-1 (IGF-1) Jantas et al, 2009). In this study, we found that the levels of Bcl-2 and p-Akt increased rapidly in the brainstem approximately 2-fold between 1-6 days after SCI in adult zebrafish (Figs.…”
Section: Long-term Survival Of Upper Motor Neurons In the Nmlf And Immentioning
confidence: 64%